2019
DOI: 10.3390/su11195219
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Corporate Social Responsibility by Consumers: Use of Organic Material and Long Working Hours of Employees

Abstract: Many previous studies on consumer choice have examined consumers’ willingness to pay (WTP) for attributes related to environmental issues. In Japan, long working hours have caused many problems, including death through overwork. However, to the best of the author’s knowledge, there are no previous studies examining WTP for the attribute related to long working hours in Japan. Therefore, this study aims to examine whether consumers prefer products without involving employees’ working long hours and to demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Choosing the target product is essential for reliable results [29,78,79], responding to neutrality criteria as much as possible, i.e., usable equally by all individuals, regardless of socioeconomic and demographic conditions, such as shower gel (basic hygiene of individuals of any gender and age), unisex clothing, or towels. In the case of…”
Section: Target Product Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choosing the target product is essential for reliable results [29,78,79], responding to neutrality criteria as much as possible, i.e., usable equally by all individuals, regardless of socioeconomic and demographic conditions, such as shower gel (basic hygiene of individuals of any gender and age), unisex clothing, or towels. In the case of…”
Section: Target Product Selectionmentioning
confidence: 99%
“…Choosing the target product is essential for reliable results [29,78,79], responding to neutrality criteria as much as possible, i.e., usable equally by all individuals, regardless of socioeconomic and demographic conditions, such as shower gel (basic hygiene of individuals of any gender and age), unisex clothing, or towels. In the case of inhomogeneous goods, such as lipstick (mainly used by a female population), this should be considered when selecting the sample and analysing the results to avoid falsification and biases.…”
Section: Target Product Selectionmentioning
confidence: 99%
“…This research has identified several research gaps based on which the future research directions are provided. In experimental studies, many papers have used hypothetical scenarios (e.g.,Nakano, 2019;Ritchie et al, 2021; Rousseau & Vranken, 2013), which might not correspond to the situations in which the consumers make choices in the real markets.The sample used in certain studies is not large enough (e.g., DelGiudice et al, 2018;Kashif & Rani, 2021;Nikoli c et al, 2021;Stanco & Lerro, 2020), causing challenges of generalizability. Studies have also focused on a particular geographic region, especially developed countries (e.g.,Boccia et al, 2018;Boccia & Sarno, 2019;Lee & Chen, 2019; …”
mentioning
confidence: 99%